Fat necrosis: A consultant’s conundrum - Majithia, Jinita; Haria, Purvi; Popat, Palak; Katdare, Aparna; Chouhan, Sonal; Gala, Kunal Bharat; Kulkarni, Suyash; Thakur, Meenakshi (Frontiers in Oncology, 2023)
Fat Necrosis of the breast is a benign non-suppurative inflammation of the adipose tissue and often mimics breast cancers, posing a diagnostic challenge for the clinician and radiologist. It has a myriad of appearances on different imaging techniques, ranging from the pathognomic oil cyst and benign dystrophic calcifications, to indeterminate focal asymmetries, architectural distortions and masses. A combination of different modalities can assist a radiologist in reaching a logical conclusion to avoid unnecessary interventions. The aim of this review article was to provide comprehensive literature on the various imaging appearances of fat necrosis in the breast. Although a purely benign entity, the imaging appearances on Mammography, Contrast-Enhanced Mammography, Ultrasound and Magnetic Resonance Imaging can be quite misleading especially in post-therapy breasts. The purpose is to provide a comprehensive and an all-inclusive review on fat necrosis with a proposed algorithm allowing a systematic approach to diagnosis.